Hot hole transfer from Ag nanoparticles to multiferroic YMn2O5 nanowires enables superior photocatalytic activity. Issue 11 (7th March 2022) - Alam, Kazi M.; Gusarov, Sergey; Supur, Mustafa; Kumar, Pawan; Kobryn, Alexander E.; Cui, Kai; McCreery, Richard L.; Shankar, Karthik
Abstract : Low bandgap YMn2 O5 nanowires decorated with Ag nanoparticles show dramatic enhancement in photocatalytic activity for 4-NBT to DMAB transformation due to improved charge separation and more efficient phonon-assisted damping of Ag plasmons. Abstract : Plasmonic hot carriers with a nonthermal distribution of kinetic energies have opened up new avenues in photovoltaics, photodetection and photocatalysis. While several articles have reported ultrafast hot electron injection from coinage metals into n-type semiconductors across Schottky barriers and efficient subsequent utilization of injected hot electrons, reports of hot hole harvesting are comparatively rare due to the difficulty in forming Schottky junctions between p-type semiconductors and high work function metals. In this work, we report the fabrication, characterization and theoretical calculations of a novel integrated multiferroic-plasmonic system comprising YMn2 O5 nanowires decorated on their surface with Ag nanoparticles (NPs). A Schottky barrier for holes exists at the YMn2 O5 –Ag hetero-interface and hot holes are injected from Ag across this barrier. The synthesized hybrid along with bare Ag NPs were tested for Raman surface photocatalytic reduction of 4-NBT (4-nitrobenzenethiol) to DMAB ( p, p ′-dimercaptoazobenzene) where the composite demonstrated superior activity compared to the bare metal. Ultraviolet photoelectron spectroscopy (UPS) revealed a significantly reduced work function of the composite compared to the pristine Ag, indicative of more energetic hot electrons on the surface of the composite required for efficient photoreduction. Density functional theory (DFT)-based calculations revealed localization of molecular orbitals supportive of a possible hole transfer from YMn2 O5 to Ag and a reorganization of electronic states, which promotes increased phonon-mediated sp-intraband damping of the plasmon. DFT results also indicated a purely electronic contribution to the ferroelectric polarization of YMn2 O5 over and above the ionic contribution, which originated from the magnetic polarization of O2p states.